Coagulopathy and haemorrhage in human victims of Bothrops jararaca envenoming in Brazil. - Kamiguti, A; Cardoso, J; Theakston, R; Sano-Martins, I; Hutton, R; Rugman, F; Warrell, D; Hay, C (1991)
Thirty-four patients envenomed by Bothrops jararaca in Brazil were studied. Of these, 20 (59%) had incoagulable blood associated with local and/or systemic bleeding and 10 of the 20 were thrombocytopenic. Among 14 patients with coagulable blood, 6 (43%) had bleeding symptoms and 3 (21%) were thrombocytopenic. High levels of von Willebrand factor (vWF), plasminogen activator inhibitor type 1 (PAI-1) and tissue type plasminogen activator (t-PA) antigens were also recorded in some patients with systemic bleeding with or without incoagulable blood. These substances may have been released from endothelial cells. Admission serum venom antigen levels were similar in both groups. The study indicated that systemic haemorrhage may occur in patients with coagulable blood and thrombocytopenia and that coagulopathy is not therefore the primary cause of haemorrhage.